IMPROVING THE PROCESS AND LEARNING OUTCOMES IN MATHEMATICS USING THE COOPERATIVE LEARNING MODEL TYPE TGT - Mahdi, Muhammad; Habibie, Zulqoidi R; Apdoludin, Apdoludin (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study was motivated by the low learning process and outcomes of mathematics among fifth-grade students at SDN 196/II Taman Agung, as indicated by the lack of student involvement in classroom activities and the average exam scores that were still below the Learning Objective Achievement Criteria (KKTP) of 70. The purpose of this research is to describe improvements in the learning process and outcomes through the application of the Teams Games Tournament (TGT) Cooperative Learning Model. The research employed a Classroom Action Research (CAR) method carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 20 fifth-grade students, with data collected through observation and testing using observation sheets and test instruments. Observation data were analyzed descriptively, while test data were analyzed using simple statistical formulas. The findings indicate that the implementation of the TGT Cooperative Learning Model in learning fractions and integers was categorized as Very Good, where teacher performance in Cycle I reached 83.33% and student participation increased from 60% in Cycle I to 80% in Cycle II, exceeding the success indicator of 75%. Furthermore, student learning outcomes improved significantly above the KKTP standard of 70, with mastery learning scores increasing from 75% in Cycle I to 85% in Cycle II. These results show that the application of the TGT Cooperative Learning Model can effectively enhance both the learning process and outcomes of mathematics for fifth-grade students at SDN 196/II Taman Agung.